Aerobic biodegradation of oil and grease in palm oil mill effluent using consortium of microorganisms - Jameel, Ahmad Tariq; Abass Olanrewaju, Alade (IIUM Press, 2011)
The current methods adapted for the treatment of Palm Oil Mill Effluent (POME) in most of the palm oil mills are not very effective in treating the pollutants in the POME to the stringent standards required. Furthermore the status and concentration of oil and grease after the treatment processes is given less attention and this suggests that these approaches employed are not sustainable to minimize the environmental impact of oil and grease in POME. Moreover, the range of concentration of oil and grease in POME is relatively higher than those obtained in toxic wastewaters, thus, the need for affective treatment process for POME. Treating POME through aerobic biodegradation process with consortia of microorganisms will facilitate effective conversion of the oil and grease present in POME to environmentally safe biomass thereby rendering the wastewater safe for effective reuse in the oil palm mills and eventual safe discharge.